Ethical and juridical implications relating to biotechnology with eugenics purposes - Emaldi Cirión, Aitziber (Acta Bioethica, 2015)
New biotechnological advances associeted with reproduction raise bioethical and legal issues. Indeed, as reproductive choices proliferate, ethical conflicts favoring eugenics: embryo selection with terapheutic purposes, sex selection of the person to be born, embryo selection as a therapy for third people and so on arise. In this article, both bioethical and legal issues regarding bioetechonology associated with reproduction will be analysed.